Jihadism: online discourses and representations - Lohlker, Rüdiger (Studying jihadism, 2013)
Jihadi online media try to mobilize, recruit, and disseminate the messages of jihadi subcultures. Understanding the mechanisms and structures of the products of these online media is essential for understanding jihadism in general. Original research into visual representations of jihadi media outlets, the subtleties of jihadi videos, the specific ways jihadis use Islamic religious language, into jihadi poetry, and the ways jihadis stage their concepts in videos of kangaroo trials is presented in this volume. Jihadis as part of the imagery of global media production is another aspect of representations of jihadism described in one of the contributions